Islamic Educational Perspectives and the Use of Pa’doangan in the Mandar Community of Majene, West Sulawesi - Fathani, Hamzah S.; Darwis, Darwis; Nuari, Fabry (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2025)
This study explores the Islamic educational perspective on pa’doangan and its application within the Mandar community of Majene. Employing a qualitative research design, the study integrates both phenomenological and historical approaches. Data were collected through interviews, participant observation, and document analysis. The data were then analyzed using descriptive qualitative methods. The findings reveal that the Islamic educational outlook on pa’doangan is reflected in the everyday practices of the Mandar Majene community, particularly in the context of work and livelihood. While Islamic teachings emphasize the importance of supplication (doa) as a means to seek well-being and divine guidance, the Mandar people, especially those in Majene Regency, express similar intentions through the tradition of pa’doangan. These prayers, deeply rooted in local cultural heritage, are performed with the hope of attaining goodness and warding off harm in their professional and economic activities. In the social and occupational life of the Mandar community, the use of pa’doangan is integrally tied to their core livelihoods. These include five key domains: Pangngumang (agriculture), Pattigasang (fishing), Posasiang (seafaring), Pattukangan (craftsmanship or construction), and Pa’dagangan (trading). Each of these occupational spheres has long been embedded in the cultural fabric of Mandar society. Because these livelihoods are central to the community’s survival and identity, they are accompanied by continual hopes for success, safety, and protection from any misfortune or disruption that may arise.